ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERINGS - Wirajunayasa, Putu Agus Agung; Putri, I.G.A.M Asri Dwija (E-Jurnal Akuntansi, 2017)
This research was conducted at a company that does Initial Public Offerings (IPO) and listed in Indonesia Stock Exchange 2008-2012 period with the period 2007-2015 financial statements. The number of samples in this study were 61 companies using purposive sampling. Data analysis technique used is a different test. The ratio used as a variable in this study is the Return on Assets (ROA) and Net Profit Margin (NPM). Based on the analysis found that there are differences in the company's financial performance in the ROA ratio but can not be differences in financial performance in the ratio of NPM. In ROA visible difference in the third and fourth year after the IPO, but these differences showed declining financial performance. In NPM ratio can not be differences, but the financial performance of this ratio decreases seen from the average value before the IPO.
Keywords: IPO, Financial Performance, ROA, NPM